2020
DOI: 10.1111/jace.17586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixing glass frits on electrical property and microstructure of sintered Cu conductive thick film

Abstract: The resistivity of the sintered Cu thick film decreases with the weight percentage of the SiO2–ZnO–B2O3 additive in the mixing glass frits up to 50 wt%. As the weight percentage of the SiO2–ZnO–B2O3 additive in the mixing glass frits is over 50 wt%, the resistivity of the sintered Cu thick films is quite similar. The lowest resistivity (6.62 × 10−6 Ω‐cm) of the sintered Cu thick films occurs at 75 wt% of the SiO2–ZnO–B2O3 additive. Also, we observe the extensive glass phase framing around the large Cu grains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Thus, recently, the Cu conduction lines produced with a high density of the twin boundaries have attracted great attention due to its unique properties in the conductivity and electro-migration resistance [ 12 , 13 , 14 ]. Twin boundaries in the Cu phase can be produced by either mechanical or annealing treatment, which are called mechanical twin and annealing twins, respectively [ 15 , 16 , 17 , 18 , 19 , 20 ]. Furthermore, many researchers reported that twin boundaries can be produced by means of the electroplating [ 9 , 12 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, recently, the Cu conduction lines produced with a high density of the twin boundaries have attracted great attention due to its unique properties in the conductivity and electro-migration resistance [ 12 , 13 , 14 ]. Twin boundaries in the Cu phase can be produced by either mechanical or annealing treatment, which are called mechanical twin and annealing twins, respectively [ 15 , 16 , 17 , 18 , 19 , 20 ]. Furthermore, many researchers reported that twin boundaries can be produced by means of the electroplating [ 9 , 12 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%